Pengaruh Pengembangan Sumber Daya Manusia terhadap Kinerja Pegawai pada Kantor Desa Salamrejo Kecamatan Binangun Kabupaten Blitar - Sulistyo Anjarwati; Sutowo (LPPM STISIP IMAM BONJOL, 2026)
This study aims to analyze the effect of Human Resource Development on Employee Performance at the Salamrejo Village Office, Binangun District, Blitar Regency. A quantitative research approach was employed. The research population comprised all village officials, and a saturated sampling technique was applied. Data were collected using a Likert-scale questionnaire constructed based on human resource development indicators, including education and training, non-training activities, study assignments, and job promotion, as well as employee performance indicators encompassing quality, quantity, timeliness, attendance, and interpersonal impact. Data analysis was conducted using SPSS software, which included validity and reliability testing, classical assumption testing, simple linear regression analysis, and t-test procedures. The findings reveal that Human Resource Development has a positive and statistically significant effect on Employee Performance, as indicated by a significance value of 0.004 (p < 0.05). These results indicate that systematic and sustainable human resource development initiatives contribute to improved organizational effectiveness within village institutions and enhance the quality of public service delivery.